Lipopolysaccharide promotes tumorigenicity of hepatic progenitor cells by promoting proliferation and blocking normal differentiation. (1st February 2017) - Li, Xiao-Yong; Yang, Xue; Zhao, Qiu-Dong; Han, Zhi-Peng; Liang, Lei; Pan, Xiao-Rong; Zhu, Jing-Ni; Li, Rong; Wu, Meng-Chao; Wei, Li-Xin
Abstract: Hepatic progenitor cells (HPCs) are bipotential stem cells that can differentiate into mature hepatocytes or biliary epithelial cells (BECs). They are thought to be involved in repair of liver injury and the incidence of hepatic carcinoma. Their physiology is closely associated with the microenvironment where they reside. Lipopolysaccharide (LPS), an important component of the hepatic pathological microenvironment, is stored in the liver and affects many types of cells in various hepatosis. HPCs may also be influenced by LPS. In this paper, mouse ED13.5 E-cadherin + foetal liver cells were isolated as mouse hepatic progenitor cells (mHPCs). Proliferation of mHPCs was promoted under LPS conditions both in vivo and in vitro. Moreover, LPS enhanced colony formation ability of mHPCs, and blocked them differentiation into mature hepatocytes and formation of a bile duct-liked structure. More importantly, long-term treatment with LPS promoted tumorigenesis of mHPCs in nude mice. Thus, we conclude that LPS may promote aberrant proliferation of mHPCs and restrict their normal differentiation. Long-term exposure of mHPCs to LPS increased the risk of tumour formation. These data provide insight into the links between LPS, HPCs fate, and tumorigenesis, and present novel insight into the relationship between HPCs and their microenvironment. Highlights: To validate the correlation between LPS and HPCs. HPCs would be activated by LPS in vivo and vitro. LPS blocked normal differentiation of HPCs. Long-term treatment of LPS on HPCs would promote tumorigenesis.